ENDOVASCULAR TREATMENT OF CALCIFIED FEMOROPOPLITEAL LESIONS - Dias-Neto, Marina (2018)
Vascular calcification is a frequent finding in peripheral arterial disease and remains an additional challenge to endovascular treatment in both recanalization and durability of interventions. The lack of standardization in the classification of peripheral artery calcification has led to a defective characterization of the performance of endovascular devices in the subgroup of calcified lesions of the femoropopliteal sector. The objective of this review is to make a survey of the available evidence regarding the current options in the endovascular treatment of highly calcified lesions of the femoropopliteal sector.